Development of Animated Video on Human Digestive System Material Based on Animaker Application - Reza, Muhammad; Tambunan, Efrida Pima Sari (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
With the development of science and technology today, the learning process is not enough just to utilize learning resources and simple learning media. One way to develop learning media using technology is to develop animated learning video media. This research aims to develop animated videos based on Animaker applications, especially in Biology learning about the human digestive system. This research was conducted at Darul Qur'an Islamic Boarding School in Deli Serdang with a sample of high school class XI students. This research uses the R&D (Research & Development) method with the development of the 4D model. The development of Animaker application-based animated videos on digestive system material shows very good results with media validation results of 98.33%, material expert validation results of 90%, practitioner expert validation results of 91.46%, limited trial results with a value of 89.45% and a broad trial with a value of 88.06% obtained very valid results so that they meet the criteria very feasible to be used as learning media. Animaker application-based animated video on human digestive system material can provide new experiences, make students enthusiastic in learning, and can attract student attention and make the learning process more enjoyable.